A case report of a giant right ventricular outflow tract in a young man. Issue 45 (November 2016) - Hu, Die; Peng, Dao-Quan; Li, Xiang-Ping; Yu, Bi-Lian
Abstract: Introduction: Localized pericardium restriction is a rare disease and likely to be unrecognized owing to the atypical manifestation, even after diagnostic avenues are exhausted. Recognizing the red flags of the disease could timely spark a preliminary suspicion of the disease and thus contribute to the early application of relevant examinations. Case presentation: We will here report a case of a 21-year-old young man with a giant right ventricular outflow tract. He was presented to our hospital for further evaluation of progressive right heart failure which had been previously diagnosed as cardiomyopathy. Unlike patients with right heart failure owing to the restrictive cardiomyopathy, our patient's tissue Doppler revealed an increased early diastolic septal mitral annular velocity. In addition, the disproportion between the severity of right heart failure and the degree of myocardial dysfunction could not be completely explained by other myocardial disease, suggesting that alternative diagnosis of the patient should be sought. Subsequently, cardiac computed tomography, which revealed the focally calcific pericardium encircling the left ventricle, gave us a clue to the diagnosis of localized constrictive pericarditis. Cardiac catheterization, showing the "dip and plateau" sign, further confirmed this diagnosis. The patient underwent successful pericardiectomy. Nowadays, he is able to undertake ordinary physical activity. Conclusion: Localized constrictive pericarditis should be suspected in patients for whom the severity of heart failure and deformity of heart might not be completely explained by valvular heart disease or myocardial disease.